{Impact of a Father Figure's Presence in the Household on Children's Psychiatric Diagnoses and Functioning in Families at High Risk for Depression} - Teel, K.S. Karen Shoum; Verdeli, Helen; Wickramaratne, Priya; Warner, Virginia; Vousoura, Eleni; Haroz, Emily E.E.; Talati, Ardesheer (Journal of Child and Family Studies, 2015)
© 2015, Springer Science+Business Media New York. The consequences of living in single-parent households on children's wellbeing are well documented, but less is known about the impact of living in single-mother households among children with high familial risk for depression. Utilizing data from an ongoing three-generation study of high-risk families, this preliminary study examined a sample of 161 grandchildren of probands diagnosed with major depressive disorder, comparing those in single-parent households to those in dual-parent households with household status defined as the full-time presence of a resident male in the home. High-risk children were compared across households in terms of psychiatric diagnoses (measured by Schedule for Affective Disorders and Schizophrenia for School-Age Children; K-SADS-PL) and global functioning (assessed by Global Assessment Scale, child version; C-GAS). Results indicated that high-risk children in single-parent households had 4.7 times greater odds for developing a mood disorder and had significantly lower mean C-GAS scores (p = 0.01) compared to those in dual-parent households. Differences remained significant when controlling for household income, child's age, and either parent's depression status. There were no significant differences between high-risk children across households when household status was instead defined as legal marital status. This study has several limitations: sample size was small, probands were recruited from a clinical population, and participants had not passed completely through the period of risk for adult psychiatric disorders. These findings point towards the importance of identifying and closely monitoring children at risk for depression, particularly if they reside in households without a resident father figure.
Keywords: á marital status á; Child psychiatric diagnoses; Depression; depression á child psychiatric; diagnoses; Fathers; fathers á single mothers; Marital Status; Single mothers